ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA CV. PUTRA TUNAS MANDIRI PADANG - Gracesia Gracesia; Dewi Zulvia; Nila Sari (JURNAL PUNDI, 2017)
In carrying out the activities of companies has very much requires adannya a informed and relevant to make decisions .One of information needed is about information company accounting that are amenable to survival perusahaan.sistem accounting information the sale of and acceptance of cash is one of the sub accounting information system which explains how should the procedure in doing the sales activity and acceptance of cash from the sale , so that the act of manipulation on the sale and acceptance of cash can be avoided(Prasetiyati, 2014). Aims to determine how credits an accounting system from the sale in cv .putra mandiri shoots and to determine whether the credit the sale of an accounting system has been implemented in accordance with an accounting system theory . In an analysis of data by using the method descriptive quantitative and results in the present study show that the sale of credit accounting information system has been an important role in supporting